BITCOIN CRYPTOCURRENCY PRACTICES SHARIA MAQASHID PERSPECTIVE - Yuniartik Yuniartik (ADISAM Publisher, 2022)
Cryptocurrency is a digital currency created using cryptographic technology to secure transactions and control the creation of new units. Cryptocurrencies are not managed by any financial institution or government, so transactions made using cryptocurrencies are usually more anonymous than transactions made using fiat currency. Cryptocurrencies can be stored and exchanged through special applications or